Corporate Social Responsibility Motives in Batik Enterprises During the COVID-19 Pandemic: An Exploratory Study - Yusef Widya Karsana; Francisca Reni Retno Anggraini; Fransiscus Asisi Joko Siswanto (Universitas Muhammadiyah Yogyakarta, Indonesia, 2022)
Research aims: The study aims to describe Corporate Social Responsibility (CSR) activities by Micro, Small, and Medium Enterprises (MSMEs) during the pandemic, ascertain the CSR motives, and analyze the relationship between these motives and the characteristics of social and green entrepreneurship.Design/Methodology/Approach: This research was qualitative. Data were collected through Focus Group Discussions (FGD) with the Indonesian Batik Lovers Group (IBLG) Sekar Jagad and in-depth interviews with Batik entrepreneurs. Research findings: Batik entrepreneurs can still survive with the help of IBLG Sekar Jagad, which continued to aid through collaboration with various government agencies. Batik entrepreneurs successfully survived by modifying the employee compensation model. Regarding the prevention of environmental pollution, they still use synthetic materials, but the use has been strictly controlled. In addition, their motive for continuing to carry out CSR activities is Batik preservation.Theoretical contribution/Originality: This research provides an additional discussion on the motivation of MSMEs in CSR activities.Practitioner/Policy implication: This research provides information for the government to increase the awareness of Batik business actors to carry out CSR activities voluntarily. This study result can be used to develop MSMEs mentoring models to support social and green entrepreneurship achievement. Research limitation/Implication: The limitation of the study is that the study only involved three informants from the Batik enterprise actors, so the conclusions are only based on the interviews of these three informants.